1996
DOI: 10.1136/gut.38.5.655
|View full text |Cite
|
Sign up to set email alerts
|

High amplitude contractions in the middle third of the oesophagus: a manometric marker of chronic alcoholism?

Abstract: Background-Oesophageal motor abnormalities have been reported in alcoholism. Aim-To investigate the effects of chronic alcoholism and its withdrawal on oesophageal disease. Patients-23 chronic alcoholic patients (20 men and three women; mean age 43, range 23 to 54). Methods-Endoscopy, manometry, and 24 hour pH monitoring 7-10 days and six months after ethanol withdrawal. Tests for autonomic and peripheral neuropathy were also performed. Motility and pH tracings were compared with those of age and sex matched c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
5
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 24 publications
0
23
5
4
Order By: Relevance
“…Gastroesophageal reflux is also facilitated in chronic alcoholics due to the existence of esophageal peristaltic dysfunction, with an increase in amplitude of the contractions in the middle third of the esophagus and a decrease in the lower/ middle amplitude ratio (7). Interestingly, despite the increased gastroesophageal reflux in chronic alcoholics, such patients often present a hypertensive lower esophageal sphincter (7).…”
Section: Effects Of Alcohol Consumption Upon the Esophagusmentioning
confidence: 96%
“…Gastroesophageal reflux is also facilitated in chronic alcoholics due to the existence of esophageal peristaltic dysfunction, with an increase in amplitude of the contractions in the middle third of the esophagus and a decrease in the lower/ middle amplitude ratio (7). Interestingly, despite the increased gastroesophageal reflux in chronic alcoholics, such patients often present a hypertensive lower esophageal sphincter (7).…”
Section: Effects Of Alcohol Consumption Upon the Esophagusmentioning
confidence: 96%
“…109,110 Oesophageal dysmotility has been reported to persist in individuals with ongoing alcoholism while normalizing in those who abstain from alcohol. 111,112 Among the inflammatory processes causing oesophageal dysphagia is eosinophilic oesophagitis, which is frequently seen in children and is now recognized in adults as a cause of solid food dysphagia and food impaction. 113 >50% of patients who present with food impaction to the emergency room have eosinophilic oesophagitis.…”
Section: Mechanical Causesmentioning
confidence: 99%
“…40 The instillation of alcohol into the stomach or duodenum of opossums while awake also produces intense bursts of spike potential (phase 3-like activity) in the duodenum and OS, 41 and a recent study in humans showed that perfusion of the descending duodenum with various ethanol-containing solutions stimulated clustered contractions that migrated aborally. 42 There is evidence of severe damage to nerves and ganglia in patients with AP.…”
Section: Motility Disturbancesmentioning
confidence: 97%